Some Side Notes on a Possible Elemental Semiotics - Silvestri , Filippo (E|C, 2023)
The present study moves from a theoretical alignment with Merleau-Ponty’s research in Le visible et l’invisible, where the French philosopher discusses Husserl’s project of foundation/return to the basic structures of the apophantic judgements regarding/in the antepredicative dimension of experience. As is known, Merleau-Ponty moves forward, aiming at a phenomenology of human-material-elemental engagement with the chair du monde, of which we are an inextricable part, beyond what are only subsequent perceptual and logical distinctions. Given these assumptions, I lay out my doubts regarding the possibility of describing an elemental semiosis (which, as such, would precede any meaningful human hypothesis), as it seems to me like a noumenon that remains beyond any semiotic pretense. Despite my doubts, at each moment of this work I have tried keeping in mind how deeply affected our semioses are by the material elements that compose them, finding also inspiration in different literary works that span Le avventure di Pinocchio and Maurice Blanchot’s thought on what he called dehors. Based also on those thoughts – which encouraged me – I chose to conclude with a theoretical opening to a type of cognitive semiotics that moves from our enactive involvement with the chair du monde.